Hyperhomocysteinemia in Chronic Kidney Disease: A Meta-Analysis - Faurin, Muthia; Deka Viotra (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Background: Hyperhomocysteinemia, an elevated level of homocysteine in the blood, has been implicated in the progression of chronic kidney disease (CKD). This meta-analysis aims to comprehensively evaluate the association between hyperhomocysteinemia and CKD and its potential impact on clinical outcomes. Methods: This study systematically searched electronic databases (PubMed, Embase, Cochrane Library) for studies published between 2018 and 2024 investigating the relationship between hyperhomocysteinemia and CKD. Studies reporting data on the association between hyperhomocysteinemia and CKD progression, cardiovascular events, or mortality were included. We extracted relevant data and performed a meta-analysis using random-effects models. Results: The meta-analysis included 25 studies comprising 5,672 patients with CKD. Hyperhomocysteinemia was significantly associated with an increased risk of CKD progression (pooled odds ratio [OR] 1.85, 95% confidence interval [CI] 1.52-2.24), cardiovascular events (pooled OR 1.63, 95% CI 1.31-2.02), and all-cause mortality (pooled OR 1.48, 95% CI 1.17-1.87) in CKD patients. Subgroup analyses revealed a consistent association across different CKD stages and etiologies. Conclusion: Hyperhomocysteinemia is an independent risk factor for CKD progression, cardiovascular events, and mortality. Monitoring and managing hyperhomocysteinemia may represent a potential therapeutic target to improve outcomes in CKD patients.